REMOTE EXPERIMENTS AS A PART OF TEACHING PROCESS - ŠEBENOVÁ, Silvia; NAGYOVÁ, Adriana (Trends in education, 2010)
Nowadays, the rapid development of informatik and communication is normal for the younger generation. ICT necessarily affect the teaching process at all levels of education, too. The contribution is dedicated to the implementation of remote real experiments in the teaching process. The project KEGA 014TTU-4/2011 Remote e-Laboratory - means of science and engineering disciplines at high school in the context of the EU in cooperation with the Hogeschool voor Wetenschap & Kunst De Nayer Instituut in Sint-Katelijne-Waver, Belgium and the Department of Technology and Information Technologies, Faculty of Education in Nitra is the intention to create a real remote experiment. The goal of this project is to measure the velocity of gaseous environment (verification of Bernoulli's equation). The contribution also provides basic information about mentioned project.
Keywords: e-learning; e-laboratory; e-research; remote experiments.